Counseling and Training Service Komputer pada Masyarakat Kelurahan Tanjung Sengkuang Kecamatan Batu Ampar Kota Batam - Larisang, Larisang; Basar, Abdul Rahman; Jarti, Nanda; Jamal, Siti Aisyah (PUAN INDONESIA, 2024)
The development of information technology, especially computers, will definitely lead to the development of users, both in terms of technology and devices. As the number of computers increases, job opportunities in the computer field will also become wider. Thus, users need to have the ability to assemble and repair computers. On the occasion of this community service activity, the Faculty of Engineering, Ibnu Sina University invited the people of Tanjung Sengkuang Village, Batu Ampar District, Batam City to provide training and counseling regarding computer repair, both hardware and software. This activity was attended by youth participants from Tanjung Sengkuang Village who are still studying Middle School and High School. The method of implementing this computer repair training activity begins with providing knowledge and demonstrating about installation and maintenance on computers. In this training, participants understand the operating system and how to repair computers, both hardware and software